Pengelolaan Lahan Berkelanjutan melalui Analisis Penjadwalan dan Kinerja Surveyor Pertanahan Menggunakan Metode Critical Path Method dan Program Evaluation and Review Technique - Awang Prayudatama; Desi Erlita; Toni Isbandi; Amellia Puspitasari; Silviani Silviani (Postgraduate Faculty, Yogyakarta Institut of Technology, Indonesia, 2026)
Land certification through the Complete Systematic Land Registration with Community Participation (PTSL PM) program is one of the Indonesian government's policy instruments in realizing legal certainty of land tenure while supporting sustainable land management. Delays in PTSL PM implementation not only affect administrative aspects but may also hinder ecosystem mapping and environmentally-based spatial conflict management. This study evaluates surveyor performance in the PTSL PM project in Srikandang Village and Banjaragung Village, Jepara Regency, through a project time management approach. Critical Path Method (CPM) was used for work network construction and critical path identification, while Program Evaluation and Review Technique (PERT) was applied for probabilistic analysis of duration uncertainty. Data were collected through field observation, in-depth interviews, and project documentation. CPM results show that the critical path in Banjaragung Village consists of activities G1–H1–I1–J1–K1–L1 with a total implementation duration of 48 days, while in Srikandang Village the critical path runs through A2–B2–C2–D2–E2–F2–G2–N2–O2–P2 with a total of 58 days. PERT analysis reveals a low risk of delay for both projects. Main obstacles identified include weather conditions, incomplete administrative documents, and limited village official assistance. This research contributes to optimizing survey project planning, ultimately supporting sustainable land management and ecosystem inventories.